Holocaust in Lithuania: anti-Jewish pogroms in Kaunas on 25–29 June, 1941 - Rukšėnas, Alfredas (Genocidas ir rezistencija, 2021)
Anti-Jewish pogroms in Kaunas on 25-29 June, 1941 is a constituent part of the first stage of the genocide of Lithuanian Jews, which covers the period between the end of June and the beginning of August, 1941. On the 25th of June, when the pogroms started, the uprising in Kaunas had just come to an end (in other locations of Lithuania it was still taking place). On the same day the armed forces of the 16th army of Army Group North marched into Kaunas, the 812 Field Commandant’s Office was established. The establishment of the German military administration meant that the functions of the highest authorities that had been carried out until that time, i. e., for a very short time, by the Provisional Government of Lithuania, fell into its hands. The Germans recognised neither the Provisional Government of Lithuania nor Lithuania’s independence declared, and they treated the local administrative authorities that were started to be re-established during the uprising as subordinate to them.
Keywords: German occupation; nazi policy; holocaust; Kaunas; collaborators